Quantifying Conflict of Interest in the Choice of Anti-VEGF Agents - Browning DJ (Dove Medical Press, 2021)
David J Browning,1 Paul B Greenberg2 1Charlotte, Eye, Ear, Nose, and Throat Associates, Charlotte, NC, 28210, USA; 2Division of Ophthalmology, Alpert Medical School, Brown University, Providence, RI, USACorrespondence: David J Browning Email djbrowning179@gmail.comPurpose: To quantify the economic incentives associated with the choice of anti-VEGF drugs for retinal diseases.Methods: An economic model was created based on the distribution of use and number of injections of bevacizumab (B), versus aflibercept or ranibizumab (AR); published Medicare reimbursement rates; published rebates; estimated unreimbursed drug use; estimated use of drug company samples; and published costs-of-drugs. Differential economic incentives associated with the choice of drugs were calculated over a range of distributions of drug use.Results: The splits in drug choice ranged from 92% AR/8% B to 31% AR/69% B, and in annual injection numbers from 2000 to 6000 with a median of 4000 in one 5-person retina service. Assumed values for rebates were 1% for drug company rebate, 1% for group purchasing organization rebate, and 5 for number of unreimbursed injections per year. The differential economic incentive of a 92% AR/8% B split compared to a 31% AR/69% B split for the median annual number of injections was $266, 893.Conclusion: Using real-world data, the economic incentive associated with a choice of more expensive anti-VEGF drugs is large. Accounting for unreimbursed drug use and the cost of additional staff required to manage expensive drug inventory does not nullify the incentive. To what degree this financial incentive influences ophthalmologists’ choice of drugs is unknown, but not trivial. Financial disclosure of the conflicts of interest in the drugs recommended for treatment should be discussed with patients.Keywords: anti-vascular endothelial growth factor agents, conflict of interest, economic incentives